The Correlation Between Classroom Management and Writing Learning Outcomes in Indonesian Language Subject for 5th Grade Elementary Students - Muhammad Saiful; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This study was motivated by the low writing achievement of Grade V students at SD Negeri 010 Hutapuli, Mandailing Natal Regency, which is suspected to be influenced by the suboptimal classroom management implemented by teachers. An unconducive learning atmosphere, ineffective student interaction, and inadequate classroom arrangement were found to negatively affect student motivation and participation in writing activities. Therefore, this research aims to examine the correlation between classroom management and students’ writing learning outcomes in Indonesian language subject. This study employed a quantitative method with a correlational approach. The population consisted of all Grade V students of SD Negeri 010 Hutapuli, totaling 40 students. The instrument used to measure classroom management was a questionnaire, while the students’ writing achievement was assessed through documentation of writing task scores. Data were analyzed using Pearson’s Product Moment correlation technique. The results showed that the correlation coefficient (r) was 0.724, which falls into the "high" category based on the interpretation guideline by Sugiyono (2007). Furthermore, the obtained value of rcount 0.724 exceeded the critical value of rtable 0.316 at the 5% significance level and 0.408 at the 1% level. Thus, the hypothesis is accepted. This indicates a significant and positive correlation between classroom management and students’ writing outcomes.The coefficient of determination analysis revealed that classroom management contributed 52% to students’ writing performance, while the remaining 48% was influenced by other factors such as learning interest, instructional media, classroom conditions, and teaching approaches. Hence, effective classroom management which includes organizing the learning environment, managing student behavior, and fostering a conducive classroom atmosphere plays a crucial role in enhancing students’ writing skills